COMORBIDITIES IN PSORIATIC ARTHRITIS: COMPARISON WITH RHEUMATOID ARTHRITIS AND PSORIASIS - Nas, K.; Karkucak, M.; Durmus, B.; Karatay, S.; Capkin, E.; Kaya, A.; Ozgocmen, S. (Clinical & Exper Rheumatology, 2014)
[Abstract Not Available]